1 - Suwandi, Muhammad Geri; Syaifuloh, Danang Arif; Kuncoro , Satrio (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2025)
In the current digital era, dependence on internet network services is increasing, especially in the context of satellite internet network services such as Spacenet. However, vulnerability to internet network service disruptions is a serious challenge faced by startup companies operating in the online buying and selling ecosystem. In this study, we conducted an in-depth analysis of the crisis that emerged due to disruption of internet network services on Spacenet and its impact on startup operations in the online buying and selling sector. We explore the causes of the crisis, the strategies implemented by startup companies to overcome these problems, and the impact on their performance and business continuity. Through a qualitative approach involving interviews with key stakeholders and secondary data analysis, we present a deeper understanding of how the crisis in internet network service disruptions can affect startups in the online buying and selling ecosystem. The results of this study provide valuable insights for industry stakeholders and can serve as a basis for the development of future risk mitigation strategies.